The legal status of church-state relationships in the United States : with special reference to the public schools - Johnson, Alvin W. (Alvin Walter), 1895-1958 (University of Minnesota Press, 1934)
The Legal Status of Church-State Relationships in the United States was first published in 1934. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.